Measuring and modeling vertical gradients in suspended sediments in the Solimões/Amazon River. Issue 3 (21st November 2016) - Armijos, E.; Crave, A.; Espinoza, R.; Fraizy, P.; Santos, A.L.M.R. Dos; Sampaio, F.; De Oliveira, E.; Santini, W.; Martinez, J.M.; Autin, P.; Pantoja, N.; Oliveira, M.; et al.
Abstract: Accurately measuring sediment flux in large rivers remains a challenge due to the spatial and temporal cross‐sectional variability of suspended sediment concentrations in conjunction with sampling procedures that fail to accurately quantify these differences. This study presents a field campaign methodology that can be used to improve the measurement of suspended sediment concentrations in the Amazon River or similarly large rivers. The turbidity signal and Rouse model are together used in this study to define the spatial distribution of suspended sediment concentrations in a river cross‐section, taking into account the different size fractions of the sediment. With this methodology, suspended sediment fluxes corresponding to each sediment class are defined with less uncertainty than with manual samples. This paper presents an application of this methodology during a field campaign at different gauging stations along a 3, 000‐km stretch of the Solimões/Amazon River during low water and flood periods. Vertical concentration profiles and Rouse model applications for distinctive sediment sizes are explored to determine concentration gradients throughout a cross‐section of the river. The results show that coupling both turbidity technology and the Rouse model may improve our understanding of the spatial distribution of different sediments fractions sizes in the Solimões/Amazon River. These data are very useful in defining a pertinent monitoring strategy for suspended sediment concentrations in the challenging context of large rivers.